THE ANALYSIS OF TASKS PRESENTED IN KURIKULUM MERDEKA TEXTBOOK ENGLISH FOR NUSANTARA - Damayanti, Irma; Mukarto, Fransiskus Xaverius (Universitas Muhammadiyah Metro, 2024)
English language textbooks play an essential role in presenting learning material and assisting students in acquiring language skills. Most Indonesian teachers heavily depend on textbooks; however, they often lack knowledge about the task types employed in textbooks. The study aims to analyze the tasks in the English textbook and the types of tasks presented in the English textbook English for Nusantara. English for Nusantara is the primary sourcebook for seventh and eighth-grade junior high school students in Kurikulum Merdeka. The analysis was conducted by utilizing Nunan's (1990) typology of tasks to determine the different categories and frequency of tasks within the textbooks. Stratified random sampling was used for this research, and tasks were taken from two different units in each textbook. The findings indicated that the textbooks comprise various types of tasks, and each of the textbooks emphasized distinct task types. The seventh-grade textbook places a greater emphasis on cognitive tasks, whereas the eighth-grade textbook places a greater emphasis on interpersonal tasks. Nonetheless, the task distribution is unbalanced, and certain categories of tasks remain unaddressed in both textbooks; specifically, creative and affective tasks are absent.